Exploring the relationship between extracurricular activities and student self-efficacy within university. Issue 9 (21st October 2021) - Griffiths, Teri-Lisa; Dickinson, Jill; Day, Catherine J.
ABSTRACT: This exploratory study addresses a gap in the literature for the potential in assessing domain-specific self-efficacy within the context of Higher Education (HE). Focusing on HE students' participation in extracurricular activities (ECAs), the study builds on the authors' previous research which recognised the impact of ECAs on HE students' lived experiences. An initial sample of two hundred and ninety-four students from a from a post-92 Higher Education Institution (HEI) in the North of England (UK) completed a survey designed to measure self-concepts of student self-efficacy, encompassing academic and social tasks, and fifty-four of those students completed a follow-up survey. The key finding was that there is a positive association between involvement in certain ECAs and self-efficacy in students within the university context. Furthermore, the results indicate a relationship between engagement with certain ECA-types and specific domains of self-efficacy. These findings have important implications in that supporting students to develop higher levels of self-efficacy specific to the university setting could have an impact on key HE outcomes, such as employability. Further research needs to be undertaken to establish if there is a causal link between involvement in ECAs and the development of self-efficacy whilst at university.